HUMAN CAPITAL DRIVERS TO SERVICE INNOVATION: EVIDENCE FROM ISLAMIC BANKING IN INDONESIA - Pertiwi, Ruspita Rani; Jannah, Syayyidah Maftuhatul; Sodik, Fajar (Bank Indonesia, 2024)
This study examines the human capital drivers and how they contribute to service innovation in Indonesian Islamic banking. A questionnaire is used to gather data from a total of 225 Islamic banking employees, and then partial least squares structural equation modeling (PLS-SEM) is applied for data analysis. Moreover, the Maqashid Sharia concept from Abu Zaharah is used to enrich the study findings from an Islamic viewpoint. The findings reveal that human capital drivers comprising leadership strategies, employee engagement, and workforce optimization have both direct and indirect positive effects on service innovation. We believe that our key contribution to the work is providing a service innovation model, where the constructs in the framework employed so far have not been studied comprehensively in the context of Islamic organizations. Furthermore, the developed model integrates more relevant factors to the construction of a strategic human capital management system that can boost service innovation in Islamic banking.